A kind of crack-resistant concrete and preparation method thereof
By using polyacrylamide-doped calcium sulfoaluminate expansion agent and hydroxyl-terminated fluoropolysiloxane/carbon nanotube composites in anti-cracking concrete, the problem of early cracking is solved and the anti-cracking ability of concrete is significantly improved. and mechanical properties.
Patent Information
- Application Number
- CN202310336948.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing crack-resistant concrete is prone to cracking in the early stage. The main reason is that the hydration reaction of the expansion agent is affected by the self-drying effect, which leads to a decrease in relative humidity, inhibits the hydration reaction of the expansion agent, thereby reducing the crack resistance of the concrete.
Calcium sulfoaluminate expansion agent doped with polyacrylamide and hydroxyl-terminated fluorine-containing polysiloxane/carbon nanotube composite material are used to maintain the high relative humidity of calcium sulfoaluminate clinker through the water retention effect of polyacrylamide and prolong its life. Hydration continues to improve the expansion performance; at the same time, by modifying the carbon nanotubes, it prevents their agglomeration and improves their dispersion and performance in concrete.
It effectively improves the crack resistance of concrete, delays the development of cracks, increases the compressive strength and splitting tensile strength, and reduces the occurrence of early cracking.
Smart Images

Figure BDA0004156727890000071 
Figure BDA0004156727890000072 
Figure BDA0004156727890000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and in particular to a crack-resistant concrete and a preparation method thereof. Background Art
[0002] Concrete is a non-homogeneous material composed of gel materials, aggregates, admixtures, water, etc. Due to its strong bearing capacity and abundant sources of raw materials, it can be formulated into building components of different strengths, properties and shapes. It is the most widely used building material in various building structures.
[0003] For related technology, reference may be made to the Chinese invention patent application with publication number CN106082812A, which discloses a crack-resistant concrete comprising the following raw materials: 100-200 parts of cement, 80-120 parts of fine aggregate stone, 100-200 parts of coarse aggregate stone, 10-60 parts of rubber particles, 50-80 parts of fly ash, 12-30 parts of microsilica powder, 10-15 parts of polyamide epichlorohydrin resin, 8-16 parts of expansion agent, and 200-300 parts of water.
[0004] With respect to the above-mentioned related technologies, the inventors believe that the following defects exist: since the water demand for the hydration reaction of the expansive agent is large, and the relative humidity inside the concrete will decrease due to the self-drying effect, at this time, as the relative humidity inside the concrete decreases, the hydration reaction of the expansive agent will be inhibited, resulting in a decrease in the crack resistance of the concrete, which will cause cracking in the early stage of the concrete. Summary of the invention
[0005] In order to improve the crack resistance of concrete, the present application provides a crack-resistant concrete and a preparation method thereof.
[0006] The present application provides a crack-resistant concrete adopting the following technical solution:
[0007] A crack-resistant concrete, the raw materials comprising by weight:
[0008] 380-450 parts of cement;
[0009] 10-14 parts of calcium sulphoaluminate expansion agent doped with polyacrylamide;
[0010] 17-25 parts of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material;
[0011] 0.8-1.5 parts of water reducing agent;
[0012] 1100-1300 parts coarse aggregate;
[0013] 800-900 parts of fine aggregate;
[0014] 8-12 parts fly ash;
[0015] 1-3 parts of air entraining agent;
[0016] 140-220 parts water;
[0017] The raw materials of the calcium sulphoaluminate expansion agent doped with polyacrylamide include the following components: 50-65 parts of high-alumina cement raw material, 5-7 parts of non-ionic polyacrylamide, and 1.8-3 parts of gypsum mineralizer.
[0018] By adopting the above technical scheme and the method of doping polyacrylamide, the water-retaining effect of polyacrylamide can prompt the calcium sulphoaluminate clinker to maintain a high internal relative humidity for a long time, keep the hydration of the calcium sulphoaluminate expansive agent continuous, and achieve the purpose of improving the expansion performance of the calcium sulphoaluminate expansive agent, thereby improving the crack resistance of concrete.
[0019] Preferably, the raw materials of the terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material include the following components: 10-20 parts
[0020] Multi-walled carbon nanotubes, 2-3 parts of terminal hydroxyl fluorinated polysiloxane, 40-60 parts of anhydrous ethanol, and 200-300 parts of deionized water.
[0021] By adopting the above technical scheme, the terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material is adopted because the multi-walled carbon nanotubes are added to the concrete, which has an enhancing effect on the compressive strength and splitting tensile strength of the concrete. At the same time, the multi-walled carbon nanotubes can also be combined with cement hydration products to bridge the microcracks in the concrete and improve the aggregate interface transition zone, forming a certain adhesion structure between the microcracks, delaying the expansion of the microcracks, and thus improving the fracture performance of the concrete. However, due to the high surface energy of the multi-walled carbon nanotubes, agglomeration has occurred, resulting in uneven dispersion of the carbon nanotubes, making it difficult to exert their performance. Therefore, by modifying the carbon nanotubes with the terminal hydroxyl fluorinated polysiloxane, the surface activity of the carbon nanotubes can be reduced and the agglomeration of the carbon nanotubes can be prevented.
[0022] Preferably, the weight proportion of the ceramic fiber is 14-20 parts.
[0023] By adopting the above technical scheme, ceramic fibers are used because adding fiber materials to concrete can improve and enhance the shortcomings of concrete such as low tensile strength, small ultimate tensile strain, poor impact strength, and easy cracking. By adding ceramic fibers, not only the compressive strength of concrete can be improved, but also ceramic fibers have strong chemical resistance, can withstand acid and alkali environments for a long time, and can maintain their chemical stability in concrete, thereby improving the concrete's crack resistance.
[0024] Preferably, the water reducing agent is calcium lignin sulfonate.
[0025] By adopting the above technical solution, the use of water reducing agent can improve the fluidity, strength and durability of concrete. Calcium lignin sulfonate is used as a concrete water reducing agent, which has an adsorption and dispersion effect on cement, can improve various physical properties of concrete, and at the same time, without changing the water consumption of concrete, can increase the fluidity of concrete, improve workability and improve the quality of the project.
[0026] Preferably, the air entraining agent is a rosin soap type air entraining agent.
[0027] By adopting the above technical scheme, air-entraining agent is used because the air-entraining agent can introduce a large number of uniformly distributed, stable and closed tiny bubbles during the mixing process, thereby improving the workability and durability of concrete. Rosin soap-type air-entraining agents have good foaming properties, uniform and stable bubbles, and can improve the slump, fluidity and plasticity of concrete.
[0028] The present application also provides a method for preparing crack-resistant concrete using the following technical solution:
[0029] A method for preparing crack-resistant concrete comprises the following steps:
[0030] 380-450 parts of cement, 10-14 parts of calcium sulphoaluminate expansion agent doped with polyacrylamide, 17-25 parts of terminal hydroxyl fluorine-containing polysiloxane / carbon nanotube composite material, 14-20 parts of ceramic fiber, 1100-1300 parts of coarse aggregate, 800-900 parts of fine aggregate, 8-12 parts of fly ash and 1-3 parts of air entraining agent are stirred and mixed uniformly; then 140-220 parts of water and 0.8-1.5 parts of water reducing agent are added, and the mixture is stirred uniformly to obtain crack-resistant concrete.
[0031] By adopting the above technical scheme, a calcium sulphoaluminate expansion agent doped with polyacrylamide is used in combination with a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material. The terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material can coordinate and restrain the expansion of the calcium sulphoaluminate expansion agent doped with polyacrylamide, thereby offsetting external loads and delaying the development of cracks.
[0032] Preferably, the method for preparing the calcium sulphoaluminate expansion agent doped with polyacrylamide comprises the following steps:
[0033] Dissolve 5-7 parts of nonionic polyacrylamide in 10-15 parts of water to obtain a nonionic polyacrylamide solution; mix and calcine 50-65 parts of high-alumina cement raw materials and 1.8-3 parts of gypsum mineralizer to obtain calcium sulfoaluminate clinker; grind the obtained calcium sulfoaluminate clinker finely, add the nonionic polyacrylamide solution and mix evenly; and dry to obtain a calcium sulfoaluminate expansion agent doped with polyacrylamide.
[0034] By adopting the above technical solution and using polyacrylamide doped with calcium sulphoaluminate expansion agent, the calcium sulphoaluminate clinker can be made to maintain a relatively high internal relative humidity for a long time, thereby improving the expansion performance of the calcium sulphoaluminate expansion agent.
[0035] Preferably, the method for preparing the hydroxy-terminated fluorinated polysiloxane / carbon nanotube composite material comprises the following steps:
[0036] S1. Add 10-20 parts of multi-walled carbon nanotubes to 200-300 parts of deionized water and disperse them in an ice water bath to obtain a dispersion A;
[0037] S2. Add 2-3 parts of terminal hydroxyl fluorinated polysiloxane to 40-60 parts of anhydrous ethanol and stir evenly, pour the mixed solution of terminal hydroxyl fluorinated polysiloxane and anhydrous ethanol into dispersion A, and continue to disperse under ice water bath conditions to obtain dispersion B;
[0038] S3. The dispersion B is subjected to reflux reaction. After the reaction is completed, the product is rinsed with acetone and ethanol in sequence and filtered. After rinsing, it is dried to obtain a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material.
[0039] By adopting the above technical solution and modifying the carbon nanotubes with terminal hydroxyl fluorinated polysiloxane, the surface activity of the carbon nanotubes can be reduced, and the carbon nanotubes can be prevented from agglomerating, thereby enhancing the compressive strength and splitting tensile strength of the concrete.
[0040] In summary, the present application includes at least one of the following beneficial technical effects:
[0041] 1. By adopting the above technical scheme, the method of doping polyacrylamide is adopted, and the water retention of polyacrylamide can be used to promote the calcium sulphoaluminate clinker to maintain a high internal relative humidity for a long time, and the hydration of the calcium sulphoaluminate expansive agent is maintained continuously, so as to achieve the purpose of improving the expansion performance of the calcium sulphoaluminate expansive agent, thereby improving the crack resistance of the concrete;
[0042] 2. By adopting the above technical solution, the terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material is adopted because the multi-walled carbon nanotubes are added to the concrete, which has an enhancing effect on the compressive strength and splitting tensile strength of the concrete. At the same time, the multi-walled carbon nanotubes can be well combined with the cement hydration products, bridge the micro cracks in the concrete and improve the aggregate interface transition zone, form a certain adhesion structure between the micro cracks, delay the expansion of the micro cracks, and thus improve the fracture performance of the concrete. However, due to the high surface energy of the multi-walled carbon nanotubes, agglomeration has occurred, resulting in uneven dispersion of the carbon nanotubes, making it difficult to exert their performance. Therefore, by modifying the carbon nanotubes with the terminal hydroxyl fluorinated polysiloxane, the surface activity of the carbon nanotubes can be reduced, and the carbon nanotubes can be prevented from agglomerating;
[0043] 3. By adopting the above technical scheme, ceramic fiber is used because adding fiber materials to concrete can improve and enhance the shortcomings of concrete such as low tensile strength, small ultimate tensile strain, poor impact strength, and easy cracking. By adding ceramic fiber, not only the compressive strength of concrete can be improved, but also ceramic fiber has strong chemical resistance, can withstand acid and alkali environment for a long time, and can maintain its chemical stability in concrete, thereby improving the concrete's crack resistance. DETAILED DESCRIPTION
[0044] The present application is further described in detail below with reference to the embodiments.
[0045] Example
[0046] Example 1
[0047] A method for preparing crack-resistant concrete comprises the following steps:
[0048] S1. Dissolve 5g of nonionic polyacrylamide in 10g of water to obtain a nonionic polyacrylamide solution; calcine 50g of high-alumina cement raw material and 1.8g of gypsum mineralizer at 1320°C for 12h to obtain calcium sulfoaluminate clinker, grind the obtained calcium sulfoaluminate clinker to a particle size of 0.06mm, add the nonionic polyacrylamide solution, stir for 20min, and dry at 200°C to obtain a calcium sulfoaluminate expansion agent doped with polyacrylamide;
[0049] S2. 10 g of multi-walled carbon nanotubes and 200 g of deionized water were poured into a beaker, and then the beaker was placed in an ultrasonic cell crusher, and ultrasonic dispersion was performed at an ultrasonic frequency of 35 Hz for 30 min in an ice water bath environment to obtain a dispersion A;
[0050] S3. Pour 40g of anhydrous ethanol into a beaker, weigh 2g of terminal hydroxyl fluorinated polysiloxane and stir evenly, pour the mixed solution of terminal hydroxyl fluorinated polysiloxane and anhydrous ethanol into dispersion A, and continue ultrasonication at an ultrasonic frequency of 35Hz for 30min in an ice water bath environment to obtain dispersion B;
[0051] S4. Pour the above dispersion B into a three-necked flask, and reflux for 24 hours at a temperature of 88°C and a rotation speed of 280rpm / min; after the reflux reaction, filter the product under a vacuum degree of 0.85MPa, first rinse it with a large amount of acetone, and then rinse it with a large amount of ethanol; after rinsing, put it into a vacuum drying oven and vacuum dry it at 100°C for 24 hours. After drying, a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material is obtained;
[0052] S5. 380g cement, 10g calcium sulfoaluminate expansion agent doped with polyacrylamide, 17g terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 14g ceramic fiber, 1100g coarse aggregate, 800g fine aggregate, 8g fly ash, 1g rosin soap air entraining agent were mixed and stirred for 10min. The coarse aggregate used in this embodiment was 20mm limestone gravel, the crushing index was 5.7%, and the bulk density was 1460kg / m 3 The fine aggregate is natural river sand with a fineness modulus of 2.8 and a mud content of <1.0%; the fly ash is Class II fly ash with a fineness of 14%, a water requirement ratio of 98.5%, and a loss on ignition of 2.25%; then 140g of water and 0.8g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring for 20 minutes.
[0053] Example 2
[0054] The difference between Example 2 and Example 1 is that the process parameters for preparing the calcium sulphoaluminate expansion agent doped with polyacrylamide in Example 2 are different, as follows:
[0055] S1. 6 g of nonionic polyacrylamide is dissolved in 13 g of water to obtain a nonionic polyacrylamide solution; 60 g of high-alumina cement raw material and 2.4 g of gypsum mineralizer are calcined at 1340° C. for 13 h to obtain calcium sulfoaluminate clinker, the calcium sulfoaluminate clinker is ground to a particle size of 0.05 mm, the nonionic polyacrylamide solution is added, the mixture is stirred for 30 min, and the calcium sulfoaluminate expansion agent doped with polyacrylamide is obtained after drying at 260° C.
[0056] Example 3
[0057] The difference between Example 3 and Example 1 is that the process parameters for preparing the calcium sulphoaluminate expansion agent doped with polyacrylamide in Example 3 are different, as follows:
[0058] S1. Dissolve 7g of nonionic polyacrylamide in 15g of water to obtain a nonionic polyacrylamide solution; calcine 65g of high-alumina cement raw material and 3g of gypsum mineralizer at 1360°C for 14h to obtain calcium sulfoaluminate clinker, grind the obtained calcium sulfoaluminate clinker to a particle size of 0.04mm, add the nonionic polyacrylamide solution, stir for 40min, and dry at 300°C to obtain a calcium sulfoaluminate expansion agent doped with polyacrylamide.
[0059] Example 4
[0060] The difference between Example 4 and Example 1 is that the process parameters for preparing the hydroxyl-terminated fluorinated polysiloxane / carbon nanotube composite material in Example 4 are different, as follows:
[0061] S2. 15 g of multi-walled carbon nanotubes and 250 g of deionized water were poured into a beaker, and then the beaker was placed in an ultrasonic cell crusher, and ultrasonically dispersed at an ultrasonic frequency of 45 Hz for 40 min in an ice water bath environment to obtain a dispersion A;
[0062] S3. Pour 50g of anhydrous ethanol into a beaker, weigh 2.5g of terminal hydroxyl fluorinated polysiloxane and stir evenly, pour the mixed solution of terminal hydroxyl fluorinated polysiloxane and anhydrous ethanol into dispersion A, and continue ultrasonication at an ultrasonic frequency of 45Hz for 40min in an ice water bath environment to obtain dispersion B;
[0063] S4. Pour the above dispersion B into a three-necked flask, and reflux for 26 hours at a temperature of 95°C and a rotation speed of 290rpm / min; after the reflux reaction, filter the product under a vacuum degree of 0.90MPa, first rinse it with a large amount of acetone, and then rinse it with a large amount of ethanol; after rinsing, put it into a vacuum drying oven, and vacuum dry it at 110°C for 25 hours. After drying, a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material is obtained.
[0064] Example 5
[0065] The difference between Example 5 and Example 1 is that the process parameters for preparing the hydroxyl-terminated fluorinated polysiloxane / carbon nanotube composite material in Example 5 are different, as follows:
[0066] S2. 20 g of multi-walled carbon nanotubes and 300 g of deionized water were poured into a beaker, and then the beaker was placed in an ultrasonic cell crusher, and ultrasonic dispersion was performed at an ultrasonic frequency of 55 Hz for 60 min in an ice water bath environment to obtain a dispersion A;
[0067] S3. Pour 60g of anhydrous ethanol into a beaker, weigh 3g of terminal hydroxyl fluorinated polysiloxane and stir evenly, pour the mixed solution of terminal hydroxyl fluorinated polysiloxane and anhydrous ethanol into dispersion A, and continue ultrasonication at an ultrasonic frequency of 55Hz for 60min in an ice water bath environment to obtain dispersion B;
[0068] S4. Pour the above dispersion B into a three-necked flask, and reflux for 28 hours at a temperature of 88°C and a rotation speed of 300rpm / min; after the reflux reaction, filter the product under a vacuum degree of 0.95MPa, first rinse it with a large amount of acetone, and then rinse it with a large amount of ethanol; after rinsing, put it into a vacuum drying oven, and vacuum dry it at 120°C for 26 hours. After drying, a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material is obtained.
[0069] Example 6
[0070] The difference between Example 6 and Example 1 is that the process parameters for preparing crack-resistant concrete in Example 6 are different, as follows: S5. 410 g of cement, 10 g of calcium sulfoaluminate expansion agent doped with polyacrylamide, 17 g of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 14 g of ceramic fiber, 1200 g of coarse aggregate, 850 g of fine aggregate, 10 g of fly ash, and 2 g of rosin soap-based air entraining agent are mixed and stirred for 15 min. The coarse aggregate used in this example is 20 mm limestone crushed stone with a crushing index of 5.7% and a bulk density of 1460 kg / m 3 The fine aggregate is natural river sand with a fineness modulus of 2.8 and a mud content of <1.0%; the fly ash is Class II fly ash with a fineness of 14%, a water requirement ratio of 98.5%, and a loss on ignition of 2.25%; then 180g of water and 1.1g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring for 25 minutes.
[0071] Example 7
[0072] The difference between Example 7 and Example 1 is that the process parameters for preparing crack-resistant concrete in Example 7 are different, as follows: S5. 450g cement, 10g calcium sulfoaluminate expansion agent doped with polyacrylamide, 17g terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 14g ceramic fiber, 1300g coarse aggregate, 900g fine aggregate, 12g fly ash, and 3g rosin soap air entraining agent are mixed and stirred for 20min. The coarse aggregate used in this example is 20mm limestone crushed stone with a crushing index of 5.7% and a bulk density of 1460kg / m 3 The fine aggregate is natural river sand with a fineness modulus of 2.8 and a mud content of <1.0%; the fly ash is Class II fly ash with a fineness of 14%, a water requirement ratio of 98.5%, and a loss on ignition of 2.25%; then 220g of water and 1.5g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring for 30 minutes.
[0073] Embodiment 8-13
[0074] The difference between Example 8-13 and Example 1 is that the process parameters for preparing the crack-resistant concrete in Example 8-13 are different, as shown in Table 1:
[0075] Table 1 Process parameters for preparing crack-resistant concrete in Examples 8-13
[0076]
[0077]
[0078] Comparative Example
[0079] Comparative Examples 1-6
[0080] The difference between Comparative Examples 1-6 and Example 1 is that the process parameters for preparing the crack-resistant concrete in Comparative Examples 1-6 are different, as shown in Table 2:
[0081] Table 2 Process parameters for preparing crack-resistant concrete in Comparative Examples 1-6
[0082]
[0083] Comparative Example 7
[0084] The difference between Comparative Example 7 and Example 1 is that the process parameters for preparing crack-resistant concrete in Comparative Example 7 are different, specifically as follows: S5. 380g of cement, 10g of ordinary calcium sulfoaluminate expansion agent, 17g of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 14g of ceramic fiber, 1100g of coarse aggregate, 800g of fine aggregate, 8g of fly ash, and 1g of rosin soap-based air-entraining agent are stirred and mixed evenly; then 140g of water and 0.8g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring evenly.
[0085] Comparative Example 8
[0086] The difference between Comparative Example 8 and Example 1 is that the process parameters for preparing crack-resistant concrete in Comparative Example 7 are different, specifically as follows: S5. 380g of cement, 10g of calcium sulfoaluminate expansion agent doped with polyacrylamide, 17g of carbon nanotubes, 14g of ceramic fibers, 1100g of coarse aggregate, 800g of fine aggregate, 8g of fly ash, and 1g of rosin soap-based air-entraining agent are mixed and stirred for 10 minutes; then 140g of water and 0.8g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring for 20 minutes.
[0087] Comparative Example 9
[0088] The difference between Comparative Example 9 and Example 1 is that the process parameters for preparing crack-resistant concrete in Comparative Example 9 are different, specifically as follows: S5. 380g of cement, 10g of calcium sulfoaluminate expansion agent doped with polyacrylamide, 17g of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 0g of ceramic fiber, 1100g of coarse aggregate, 800g of fine aggregate, 8g of fly ash, and 1g of rosin soap-based air-entraining agent are mixed and stirred for 10 minutes; then 140g of water and 0.8g of calcium lignin sulfonate are added, and a crack-resistant concrete is obtained after stirring for 20 minutes.
[0089] Performance testing
[0090] 1. The crack-resistant concrete of Examples 1-13 and Comparative Examples 1-9 were used as test samples. After curing for 30 days, the surface of each group of samples was observed to see if there were any cracks, and the length of the cracks was recorded. The test samples were standard cubic specimens of 200 mm × 200 mm × 200 mm;
[0091] 2. The compressive strength and splitting compressive strength of the crack-resistant concrete of Examples 1-13 and Comparative Examples 1-9 were tested using GB / T50081-2002 "Test methods for mechanical properties of ordinary concrete".
[0092] The specific test results are shown in Table 3:
[0093] Table 3 Performance test results
[0094]
[0095]
[0096] It can be seen from the test results of Examples 1-3 that within the process parameter range for preparing the calcium sulfoaluminate expansive agent doped with polyacrylamide provided in the present application, the prepared calcium sulfoaluminate expansive agent doped with polyacrylamide is used for crack-resistant concrete, and the obtained crack-resistant concrete has good crack resistance, high compressive strength, and no obvious cracks are generated within 30 days of curing.
[0097] It can be seen from the test results of Examples 1, 4, and 5 that within the process parameter range for preparing the terminal hydroxyl-containing fluorinated polysiloxane / carbon nanotube composite material provided in the present application, the obtained calcium sulfoaluminate expansive agent doped with polyacrylamide is used for crack-resistant concrete, and the obtained crack-resistant concrete has good crack resistance, high compressive strength, and no obvious cracks are generated within 30 days of curing.
[0098] It can be seen from the test results of Examples 1, 6, and 7 that within the process parameter range for preparing crack-resistant concrete provided in the present application, the prepared crack-resistant concrete has good crack resistance, high compressive strength, and no obvious cracks occur within 30 days of curing.
[0099] It can be seen from the test results of Examples 1, 8, 9 and Comparative Examples 1 and 2 that when the content of calcium sulfoaluminate expansion agent doped with polyacrylamide increases, the compressive strength and splitting tensile strength of the obtained crack-resistant concrete are gradually improved. When the content of calcium sulfoaluminate expansion agent doped with polyacrylamide is less than 10 parts, obvious cracks will be generated. At 10-14 parts, no obvious cracks will be generated. When the calcium sulfoaluminate expansion agent doped with polyacrylamide exceeds 12 parts, the compressive strength and splitting tensile strength begin to decrease. When the calcium sulfoaluminate expansion agent doped with polyacrylamide exceeds 14 parts, obvious cracks will be generated again. It can be seen from the test results of Comparative Example 7 that doping with polyacrylamide improves the compressive strength and splitting tensile strength of crack-resistant concrete.
[0100] From the test results of Examples 1, 10, 11 and Comparative Examples 3 and 4, it can be seen that when the content of the hydroxyl fluorinated polysiloxane / carbon nanotube composite material increases, the compressive strength and splitting tensile strength of the obtained crack-resistant concrete gradually increase. When the content of the hydroxyl fluorinated polysiloxane / carbon nanotube composite material is less than 17 parts, obvious cracks will be generated. At 17-25 parts, no obvious cracks will be generated. When the calcium sulfoaluminate expansion agent doped with polyacrylamide exceeds 21 parts, the compressive strength and splitting tensile strength begin to decrease. When the calcium sulfoaluminate expansion agent doped with polyacrylamide exceeds 25 parts, obvious cracks will be generated again. From the test results of Comparative Example 8, it can be seen that the compressive strength and splitting tensile strength of the crack-resistant concrete are improved by compounding carbon nanotubes with hydroxyl fluorinated polysiloxane.
[0101] From the test results of Examples 1, 12, 13 and Comparative Examples 5 and 6, it can be seen that when the content of ceramic fiber increases, the compressive strength and splitting tensile strength of the obtained crack-resistant concrete gradually increase. When the content of ceramic fiber is less than 14 parts, obvious cracks will occur. When the calcium sulfoaluminate expansion agent doped with polyacrylamide exceeds 20 parts, the compressive strength and splitting tensile strength no longer change, and no obvious cracks are generated. From the test results of Comparative Example 9, it can be seen that the compressive strength and splitting tensile strength of crack-resistant concrete can be improved by adding ceramic fiber.
[0102] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A crack-resistant concrete, characterized in that: The raw materials include by weight: 380-450 parts of cement; 10-14 parts of calcium sulphoaluminate expansion agent doped with polyacrylamide; 17-25 parts of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material; 8-1.5 parts of water reducing agent; 1100-1300 parts coarse aggregate; 800-900 parts of fine aggregate; 8-12 parts fly ash; 1-3 parts of air entraining agent; 140-220 parts water; The raw materials of the calcium sulphoaluminate expansion agent doped with polyacrylamide include the following components: 50-65 parts of high-alumina cement raw material, 5-7 parts of non-ionic polyacrylamide, and 1.8-3 parts of gypsum mineralizer; The raw materials of the terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material include the following components: 10-20 parts of multi-walled carbon nanotubes, 2-3 parts of terminal hydroxyl fluorinated polysiloxane, 40-60 parts of anhydrous ethanol, and 200-300 parts of deionized water; The raw materials also include 14-20 parts by weight of ceramic fibers; The water reducing agent is calcium lignin sulfonate; The air entraining agent is a rosin soap type air entraining agent; The method for preparing concrete comprises the following steps: 380-450 parts of cement, 10-14 parts of calcium sulphoaluminate expansion agent doped with polyacrylamide, 17-25 parts of terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material, 14-20 parts of ceramic fiber, 1100-1300 parts of coarse aggregate, 800-900 parts of fine aggregate, 8-12 parts of fly ash, and 1-3 parts of air entraining agent are stirred and mixed uniformly; then 140-220 parts of water and 0.8-1.5 parts of water reducing agent are added, and the mixture is stirred uniformly to obtain crack-resistant concrete; The preparation method of the calcium sulphoaluminate expansion agent doped with polyacrylamide comprises the following steps: Dissolving 5-7 parts of nonionic polyacrylamide in 10-15 parts of water to obtain a nonionic polyacrylamide solution; mixing and calcining 50-65 parts of high-alumina cement raw material and 1.8-3 parts of gypsum mineralizer to obtain calcium sulfoaluminate clinker; grinding the obtained calcium sulfoaluminate clinker finely, adding the nonionic polyacrylamide solution and mixing evenly, and drying to obtain a calcium sulfoaluminate expansion agent doped with polyacrylamide; The preparation method of the terminal hydroxyl fluorine-containing polysiloxane / carbon nanotube composite material comprises the following steps: S1. Add 10-20 parts of multi-walled carbon nanotubes to 200-300 parts of deionized water and disperse them in an ice water bath to obtain a dispersion A; S2. Add 2-3 parts of terminal hydroxyl fluorinated polysiloxane to 40-60 parts of anhydrous ethanol and stir evenly, pour the mixed solution of terminal hydroxyl fluorinated polysiloxane and anhydrous ethanol into dispersion A, and continue to disperse under ice water bath conditions to obtain dispersion B; S3. The dispersion B is subjected to reflux reaction. After the reaction is completed, the product is rinsed with acetone and ethanol in sequence and filtered. After rinsing, it is dried to obtain a terminal hydroxyl fluorinated polysiloxane / carbon nanotube composite material.
Citation Information
Patent Citations
Anti-cracking concrete
CN106082812A
High-expansion-rate liquid expanding agent and preparation method thereof
CN110981276A
High-crack-resistance concrete for plateau environment and preparation method
CN112694299A
Antistatic polyethylene composite material as well as preparation method and application thereof
CN115710394A